The effects of term limits and yardstick competition on local government provision of health insurance and other public services: The Philippine case - Joseph J. Capuno; Stella A. Quimbo; Aleli D. Kraft; Carlos Antonio R. Tan; Vigile Marie B. Fabella (University of the Philippines, School of Economics (UPSE), 2012)
We investigate the effects of two accountability measures on the decisions of the local governments under decentralization. Using a panel of Philippine municipalities and cities in three election years, we find that term limits have negative but weak effects on the provision of health insurance coverage to poor families and on expenditures on local services. However, yardstick competition (i.e., more subsidized insurance coverage for the poor in neighboring local governments) induces them to cover more poor families, but also reduce other public expenditures. To respond to critiques of health decentralization, our results suggest that the objectives of local politicians can be aligned with those of the health sector. The key insight is the incumbent may extend health insurance coverage like a redistributive transfer to pursue reelection objectives. However, the resulting trade off between subsidized insurance coverage and other public services must be considered.
Keywords: H72; I18; H4; 330; Local governments; term limits; yardstick competition; health insurance; poor; Philippines; Dezentralisierung; Kommunale Dienstleistung; Basisgesundheitsversorgung; Armut; Anreizregulierung; Philippinen